Perilaku Narsistik Pengguna Media Sosial di Kalangan Mahasiswa dan Implikasi dalam Layanan Bimbingan Dan Konseling - Trisna Gustia Rahman; Asmidir Ilyas (Universitas Negeri Padang, 2020)
This research is motivated by the phenomenon of students who actualize themselves through social media to get recognition from others. If done excessively it can lead to narcissistic behavior. This study aims to describe the narcissistic behavior of social media users based on aspects: (1) need to be accepted, (2) strong sense of self-important, (3) lack of insight into people's feelings and needs, and (4) envy of other's . This study uses quantitative methods with descriptive types. The total sample of 256 students was selected using the stratified random sampling technique. The research instrument used was the narcissistic behavior of social media users. Data were analyzed using descriptive statistical analysis techniques. The results of the study revealed: (1) the narcissistic behavior of social media users in the high enough category (2) in the aspect of need to be admired was in the fairly high category, (3) in the strong sense of self-important category in the high enough category ( 4) in the aspects of lack of insight into people's feelings and needs in the high category, and (3) in the aspect of envy of other's in the low category. Based on the research findings, it is recommended that the counselor be able to provide guidance and counseling services in the form of information services, individual counseling, group counseling, and group guidance in order to minimize the impact of narcissistic behavior that will be caused to students.